Practitioner Profile: An Interview with April Benson, Ph.D. - April Benson (Journal of Financial Therapy, 2015)
Dr. April Lane Benson is a nationally known psychologist specializing in the study and treatment of compulsive buying disorder. Dr. Benson is the editor of “I Shop, Therefore I Am: Compulsive Buying and the Search for Self” (2000), the first book in English for mental health professionals about compulsive buying disorder. Her second book, “To Buy or Not to Buy: Why We Overshop and How to Stop” (2008) presents the Stopping Overshopping model of treatment. A pilot randomized controlled trial on the efficacy of this treatment model was recently published in the Journal of Groups in Addiction & Recovery. Maintaining a private practice in New York City and a comprehensive website, www.shopaholicnomore.com, Dr. Benson also trains therapists and is frequently quoted and interviewed in print, radio, and television media.
Keywords: financial therapy; addiction; overshopping; compulsive buying